Effects of Teenage Pregnancy on School Girl Education in Primary Schools in Katuna Town Council Kabale District. - Tumwebaze, Costance (Kabale University, 2024)
Teenage pregnancy is a worldwide issue that affects developed and developing countries and limits the girls to engage in education. Early pregnancies and motherhood are contributing factors for school dropouts. In Uganda, the management does not question their assumptions in making their judgments hence, most of the girls in mixed day and boarding primary schools perform poorly. The purpose of this study was therefore investigating the effect of teenage pregnancy on academic performance among primary pupils. The study was guided by specific objectives which include determining the extent to which poor physical and mental health due to teenage pregnancy affects academic performance among primary pupils, finding out the effect of reduced self-esteem due to teenage pregnancy on academic performance among primary pupils, and assessing the relationship between social isolation due to teenage pregnancy and academic performance among primary pupils. The study used a case study design utilizing both qualitative and quantitative data collection and analysis methods. Using simple random and purposive sampling techniques, a total of 100 respondents were selected to participate in the study. Questionnaires and interview methods of data collection were used in this study. Based on the study findings, the majority of 90 percent were still in school meaning that being in school usually safeguards teens from becoming pregnant It was also found that 82.8% of the participants indicated that early pregnancy altered their school performance by minimizing their time of study. The study is obvious that approximately 70 percent of the participants do not agree with the media's influence on early pregnancy. On the impact of early pregnancy on life opportunities for young girls, it was found that 86 percent of participants had terminated their education. The study recommended that teenagers should be given career development which will assist them make appropriate changes from dependence to financial independence. Addressing early pregnancy, sex education should be taught in school which will enable the teenagers to know the effects of early sex engagement and early pregnancy in their educational journey and future career and life.